2016
DOI: 10.1039/c6pp00153j
|View full text |Cite
|
Sign up to set email alerts
|

Photo-induced electron transfer in a diamino-substituted Ru(bpy)3[PF6]2 complex and its application as a triplet photosensitizer for nitric oxide (NO)-activated triplet—triplet annihilation upconversion

Abstract: A system demonstrating Nitric Oxide (NO) activated Triplet-Triplet Annihilation (TTA) upconversion has been devised, based on a substituted [Ru(II)(bpy)3](PF6)2 complex (bpy = 2,2'-dipyridine) bearing a single 1,2-diaminophenyl moiety as an NO activatable triplet photosensitizer (Ru-1), and 9,10-diphenylanthracene (DPA) as a triplet acceptor/emitter. The excited triplet state of Ru-1 is significantly quenched (ΦT∼ 22%) by a Photoinduced Electron Transfer (PET) reaction, as confirmed by steady state phosphoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Tuning the excited state properties of organic chromophores is crucial for the development of various functional organic materials. The photochemical properties of a molecular system, such as the absorption and emission wavelengths, intersystem crossing (ISC), and response to an external stimuli, can be controlled by controlling the excited states . For instance, being able to control the emission of a molecule through the interaction with a specific analyte allows for the development of fluorescent molecular probes, for which the fluorescence can be switched on by the selective interaction with specific compounds. , Likewise, controlling the triplet state of a chromophore, in terms of quantum yield and lifetimes, allows for the development of targeted (or activatable) photodynamic therapy (PDT) reagents, phosphorescent molecular probes, , imaging reagents, and more recently external stimuli-responsive triplet–triplet annihilation (TTA) upconversion materials. Enhancing the light absorption by maximizing the donor/acceptor interaction through a π-conjugation is useful to develop photosensitizers for organic photovoltaics (OPV). , Charge-separated states (CSS) may form in such multichromophore molecular systems upon photoexcitation, as a storage of excitation energy, for which the electron transfer dynamics largely depend on the magnitude of the electronic coupling between the electron donor and acceptor and the interplay of the different excited states of the system …”
Section: Introductionmentioning
confidence: 99%
“…Tuning the excited state properties of organic chromophores is crucial for the development of various functional organic materials. The photochemical properties of a molecular system, such as the absorption and emission wavelengths, intersystem crossing (ISC), and response to an external stimuli, can be controlled by controlling the excited states . For instance, being able to control the emission of a molecule through the interaction with a specific analyte allows for the development of fluorescent molecular probes, for which the fluorescence can be switched on by the selective interaction with specific compounds. , Likewise, controlling the triplet state of a chromophore, in terms of quantum yield and lifetimes, allows for the development of targeted (or activatable) photodynamic therapy (PDT) reagents, phosphorescent molecular probes, , imaging reagents, and more recently external stimuli-responsive triplet–triplet annihilation (TTA) upconversion materials. Enhancing the light absorption by maximizing the donor/acceptor interaction through a π-conjugation is useful to develop photosensitizers for organic photovoltaics (OPV). , Charge-separated states (CSS) may form in such multichromophore molecular systems upon photoexcitation, as a storage of excitation energy, for which the electron transfer dynamics largely depend on the magnitude of the electronic coupling between the electron donor and acceptor and the interplay of the different excited states of the system …”
Section: Introductionmentioning
confidence: 99%
“…In the previous section, we have shown that the fluorescence of the perylene unity was quenched to a large extent by FRET occurring in the dyad. As a result, this dyad is an ideal compound for studying the effects of FRET in covalently linked photosensitizer–triplet acceptors on the resulting TTA upconversion and may also function as a TTA upconversion system which can be activated (i.e., enhanced or switched on) by an external stimulus such as light or biologically significant small organic molecules. Hence, we first studied the change in FRET (i.e., the fluorescence changes of the perylene unit in dyad BP-1 ) upon cleavage of the disulfide bond via thiol exchange in the presence of other thiols. Upon the addition of differing amounts of thiols, the UV–vis absorption spectra did not change (Figure a), in agreement with the lack of any significant interaction between the diiodoBodipy and the perylene units in the ground state.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, great efforts have been devoted to developing novel activatable triplet PSs for satisfying various applications, such as targeted photodynamic therapy (PDT), phosphorescent probe, activatable TTA-UC systems for advanced bioimaging, biosensing, chemosensing, etc. In general, the triplet state is originated from a singlet excited state via intersystem crossing (ISC), so activatable triplet PSs are normally achieved by controlling the singlet state before the ISC process. For example, an acidic pH-activatable targeted PS was synthesized by Ju’s group through attaching a dimethylaminophenyl moiety onto the meso-position of rubyrin to achieve selective and highly efficient PDT for cancer treatment. The singlet state energy of this sensitizer is quenched by a very fast intramolecular electron transfer process at physiological pH, and the ISC process is then stopped.…”
Section: Introductionmentioning
confidence: 99%
“…For these triplet PSs, controlling their triplet decay may be a good method for developing activatable triplet PSs. Unfortunately, only one activatable triplet PS that worked on this principle is reported so far, , in which an amino group acts as an electron donor to quench the triplet state of bipyridyl ruthenium.…”
Section: Introductionmentioning
confidence: 99%